(untitled) (Medical Forum Monthly, 2022)
Objective: To determine the accuracy of Early Onset Sepsis (EOS) risk calculator by following blood culture reports and CRP for predicting EOS in neonates with 34 weeks or more gestational age. Study Design: prospective observational study Place and Duration of Study: This study was conducted at the National Institute of Child Health, Karachi from April, 2022 to July, 2022. Materials and Methods: All newborns with suspected EOS presented with 34 weeks or more gestational age of either gender on empiric antibiotics during past 3 days were enrolled. Early onset neonatal sepsis risk calculator was calculated using Kaiser Permanente calculator. Results: Of 249 neonates, EOS risk calculator shows that 60 (24.1%) had clinical illness whereas 63 (25.3%) patients had well appeared status and 126 (50.1%) had equivocal status. A significantly higher risk of clinical illness was observed in low birth-weight neonates (p= 0.026), lower gestational age (p= 0.007), higher maternal temperature, having rupture of membrane (p= <0.001), higher duration of rupture of membrane (p= <0.001), GBS in any trimester (p= <0.001), >4 hours of broad-spectrum antibiotics (p= <0.001), lower oxygen saturation (p= <0.001), respiratory distress (p= 0.003), APGAR score <7 (p= <0.001), positive blood culture (p= <0.001), and positive CRP (p= <0.001). Conclusion: EOS risk calculator has highlighted around one fourth of neonates with the high risk of clinical illness in neonates presented with ≥ 34 weeks of gestational age.